2021
DOI: 10.1088/1742-6596/2042/1/012122
|View full text |Cite
|
Sign up to set email alerts
|

Review of spectral lighting simulation tools for non-image- forming effects of light

Abstract: Light via our eyes influences visual performance, visual comfort and visual experience, but also affects several health related, non-image-forming (NIF) responses. New metrics have been developed to quantify the NIF effects of light. In order to incorporate these in lighting design practice, simulation tools are required that are able to process information about the spectral distribution of light sources and materials. However, most of the tools currently used for daylight and electric light simulations simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Thirdly, as stressed by Gkaintatzi-Masouti et al [68] and Inanici et al [46], a limiting factor of the present study is also the limitations of the sky model implemented in the ALFA tool. The results presented by Inanici et al demonstrated that ALFA's atmospheric sky model underestimates the CCT variability of the sky when compared to high dynamic range photography of the real sky.…”
Section: What Are the Limitations Of The Study?mentioning
confidence: 85%
“…Thirdly, as stressed by Gkaintatzi-Masouti et al [68] and Inanici et al [46], a limiting factor of the present study is also the limitations of the sky model implemented in the ALFA tool. The results presented by Inanici et al demonstrated that ALFA's atmospheric sky model underestimates the CCT variability of the sky when compared to high dynamic range photography of the real sky.…”
Section: What Are the Limitations Of The Study?mentioning
confidence: 85%
“…For this study, it was decided to calculate the melanopic contributions according to the CIE standard and the WELL recommendations, expressing them in mel-EDI [lux] since they are a "consistent" quantity directly linked to the illuminance [43]. Others simulation tools for NIF effects of light can be investigated in this literature review [44].…”
Section: Introductionmentioning
confidence: 99%